Hybrid polystyrene/polybutadiene latexes with low environmental impact - Ronco, Ludmila Irene (2015)
The incorporation of polybutadiene in waterborne polystyrene nanoparticles by miniemulsion polymerization has the capacity of positive combining the properties of both materials, improving the toughness of the final product. Unfortunately, the polymerization does not proceed to completion, and there is inevitably a high level of unreacted monomer remaining in the polymer latexes. This work addresses the implementation of different post-treatment methods to efficiently remove the residual styrene from high solid content (50%) polybutadiene/polystyrene latexes. Two post-treatment methods were investigated: i) post-polymerization with redox initiators; and ii) post-polymerization by thermal self-initiation of styrene at high temperature (≥ 120 ºC). The effect of both post-treatment strategies on volatile organics content, latex stability, polymer microstructure, particle morphology and mechanical properties of hybrid materials was investigated. The mechanisms responsible for these effects were here discussed.